Algae Oil Treatment Protects Retinal Ganglion Cells (RGCs) via ERK Signaling Pathway in Experimental Optic Nerve Ischemia - Tzu-Lun Huang; Yao-Tseng Wen; Yu-Chieh Ho; Jia-Kang Wang; Kuan-Hung Lin; Rong-Kung Tsai (Marine Drugs, 2020)
Background: We investigated the therapeutic effects and related mechanisms of algae oil (ALG) to protect retinal ganglion cells (RGCs) in a rat model of anterior ischemic optic neuropathy (rAION). Methods: Rats were daily gavaged with ALG after rAION induction for seven days. The therapeutic effects of ALG on rAION were evaluated using flash visual evoked potentials (FVEPs), retrograde labeling of RGCs, TUNEL assay of the retina, and ED1 staining of optic nerves (ONs). The levels of inducible nitric oxide synthase (iNOS), IL-1β, TNF-α, Cl-caspase-3, ciliary neurotrophic factor (CNTF), and p-ERK were analyzed by using western blots. Results: Protection of visual function in FVEPs amplitude was noted, with a better preservation of the P1−N2 amplitude in the ALG-treated group (p = 0.032) than in the rAION group. The density of RGCs was 2.4-fold higher in the ALG-treated group compared to that in the rAION group (p < 0.0001). The number of ED1-positive cells in ONs was significantly reduced 4.1-fold in the ALG-treated group compared to those in the rAION group (p = 0.029). The number of apoptotic RGCs was 3.2-fold lower in number in the ALG-treated group (p = 0.001) than that in the rAION group. The ALG treatment inhibited ERK activation to reduce the levels of iNOS, IL-1β, TNF-α, and Cl-caspase-3 and to increase the level of CNTF in the rAION model. Conclusion: The treatment with ALG after rAION induction inhibits ERK activation to provide both anti-inflammatory and antiapoptotic effects in rAION.